The effects of retail sustainable strategies on the sustainability of the food value chain - Araujo, Cecilia Maria Lobo de (2023)
Retail plays a strategic and influential role in the food value chain, acting as a crucial link between suppliers and consumers. It directly shapes production and consumption patterns and indirectly influences the dynamics of the food value chain. Large retail companies, driven either by stakeholder pressures or voluntarily seeking a competitive advantage, are implementing a diverse portfolio of sustainable initiatives. This study is grounded in Stakeholder Theory and the understanding of the sustainability of the triple bottom line (Donaldson & Preston, 1995; Elkington, 1997). Through three interconnected investigations, seek to address the question: "How does the implementation of sustainable initiatives by retail impact the sustainability of the food value chain?" Article 1 through a pattern-matching methodology introduces an alternative perspective for sustainability - the ecocentric management mindset. This framework offers guidance for sustainability achievement at the corporation level. It emphasizes the critical importance of recognizing, engaging with, and comprehending the social and physical environments in which firms operate ("place"). It drives a constant process of reflection and questioning about sustainability achievement, providing an alternative for corporations in their pursuit of sustainability. Article 2 presents empirical findings derived from the implementation of sustainable initiatives by a multinational retail company. The study examines three distinct sub-cases: animal welfare within the pork value chain, the Horti fruit market, and food donation initiatives. Using the lens of stakeholder theory, it assesses value creation and sustainability. The results reveal positive value creation and better levels of sustainability achievement for retail and its stakeholders, along with variations in retail behavior and engagement levels influenced by motivation for retail to implement the initiative, market dynamics, and stakeholders’ power, among other factors. Article 3 through systematic literature review delves into the concept of materiality within stakeholder theory and its implications for corporate sustainability; and examines materiality assessment through empirical data derived from sustainability reports of Carrefour in Brazil. It sheds light on the limitations of the process within the framework of stakeholder theory and proposes a novel model. This model positions "nature" and "place" as central stakeholders, alongside the firm, representing the shared purpose of the firm network. It emphasizes the importance of ongoing reflection and questioning to maintain a relevant and adaptive sustainability framework. The study concludes by summarizing the key findings and outlining potential avenues for future research in this critical intersection of retail, sustainability, and the food value chain.